Study Leave for Public Employees - Adil Abdul Sahib, Researcher. Inas; Malik Afzali, Prof. Dr. Mohsen (Basra studies journal, 2024)
Study leave is one of the most important moral rights established by the legal system for public employees in Iraq and other comparative laws. Through it, an employee is considered to be continuously in actual service, which is counted for all legal purposes, and receives a full salary if they successfully complete their studies and obtain the contracted degree. Study leave is granted to improve the efficiency of public employees in performing their duties for the public service and to ensure its regular and continuous operation, achieving the public interest. A public employee is defined as "every person entrusted with a position within the ministry's staff or a body not associated with a ministry," and the public function is defined as "a national duty and social service aimed at the public interest and serving citizens in accordance with the applicable legal rules." The public facility is defined as "a public organization owned by the state, operating under the high administration of rulers in its centralized and decentralized forms, subject to a specific legal system that satisfies the collective needs of individuals in an organized, permanent manner, ensuring equality among the beneficiaries of the public facility." The Iraqi legislator recognized the importance of study leave in developing the efficiency of public employees and raising their scientific level in the public facility. Therefore, they ensured its provision to employees who wish to obtain an undergraduate or higher degree in their field of specialization, according to the regulations specified in Article (50) of the amended Civil Service Law No. (24) of 1960, which was repealed and replaced by the provisions of Article (1) of the Civil Service Law Amendment No. (14) of 2009, as well as the regulations specified in the Study Leave Grant Instructions No. (165) of 2011. To clarify this, our research will cover the concept of study leave, its regulations, the obligations of the employee on study leave, and the issues related to its grant, along with the main problems arising from granting study leave and obtaining the degree.